Genotype × soil zinc interaction constrains grain zinc loading in a biofortified common bean under farmer management - Matumba, Annie; Nalivata, Patson C.; Lark, R. Murray; Chimungu, Joseph G.; Monjerezi, Maurice; Wilson, Lolita; Limuwa, Moses M.; Broadley, Martin R.; Ander, Louise E.; Bailey, Elizabeth H. (Frontiers in Agronomy, 2025)
Biofortified crops are deployed to combat micronutrient deficiencies, but their efficacy in nutrient-poor soils is poorly understood. We evaluated the zinc (Zn) loading capacity of a biofortified bean variety NUA45 across nine smallholder-managed sites in Malawi with contrasting soil Zn status. NUA45 frequently failed to achieve its target grain Zn concentration (56 mg kg-¹), with grain Zn strongly correlated with soil Zn availability (R = 0.419, p < 0.001). In contrast, local varieties, though not bred for enhanced Zn, often accumulated higher grain Zn concentrations, averaging 8.5 percent more than NUA45, and showed no dependence on soil Zn status (R = -0.019, p = 0.939). Across 78% of the sites had soils with DTPA-extractable Zn below the agronomic threshold of 1 mg kg-¹. The analysis revealed a significant genotype × soil Zn interaction (p = 0.043) indicating that soil factors strongly modulate the expression of biofortified traits. These findings reveal that biofortified genotypes alone cannot ensure adequate Zn accumulation where soil Zn is limiting. Integrated interventions combining soil management, Zn fertilization, and breeding for enhanced translocation efficiency are therefore required to achieve nutritional targets in legumes and other smallholder crops globally.